Strategi Penanggulangan Tindak Pidana Penganiayaan (Studi Kasus Kepolisian Sektor Nusaniwe) - Werluka, Natalia; Wadjo, Hadibah Zachra; Salmon, Harly Cliford Jonas (SANISA: Jurnal Kreativitas Mahasiswa Hukum, 2026)
Introduction: This study discusses strategies for addressing assault crimes within the jurisdiction of the Nusaniwe Police Sector, focusing on the obstacles faced by police officers due to uncooperative public participation in law enforcement. The background to this research is based on the high number of assault cases influenced by alcohol consumption, social conflict, and low public participation in providing information to the police. These conditions hamper the investigation and inquiry process, resulting in suboptimal law enforcement against assault crimes.Purposes of the Research: The purpose of this study is to determine the obstacles faced by the police in dealing with uncooperative communities in criminal acts of assault and to analyze the strategies used by the Nusaniwe Sector Police in dealing with these crimes.Methods of the Research: The research method used was empirical legal research with a qualitative descriptive approach. The research location was the Nusaniwe Police Sector. Data were obtained through interviews, observations, and documentation studies. The informants in this study consisted of the Head of Criminal Investigation Unit, assistant investigators, Bhabinkamtibmas (community police officers), religious leaders, youth leaders, and neighborhood heads within the jurisdiction of the Nusaniwe Police Sector. The data obtained were then analyzed qualitatively to describe the actual conditions on the ground.Results / Findings / Novelty of the Research: The results of the study indicate that the main obstacle in handling criminal acts of assault is the uncooperative attitude of the community, such as reluctance to be witnesses, fear of dealing with the police, and the existence of family relationships with the perpetrators so that they try to protect the perpetrators. Other factors that influence the occurrence of assault are alcohol consumption and conflict between individuals. The strategies implemented by the police in dealing with criminal acts of assault include preventive, preemptive, and repressive approaches through cooperation between police units, optimizing the role of Bhabinkamtibmas, legal counseling, a family approach, and coordination with community leaders, religious leaders, and youth to increase public legal awareness.